PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN ONLINE(STUDI PADA DKPOP SHOP) - ATUL AWALIYAH, SEBTI (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
The rapid development of e-commerce in Indonesia has spurred competition between businesses in the virtual world. Therefore, providing the best service is an online business site efforts in creating customer satisfaction. SERVQUAL has been one of the most widely used scales for measuring service quality. From the traditional model of SERVQUAL Zeithaml, et al (1985) successfully developed five main dimensions of service quality, to seven e-SERVQUAL dimensions wich consist of efficiency, reliability, fulfillment, privacy, responsiveness, compensation and contact. The result of this research showed that the simultaneous independents variable service quality (X) have effect on dependents variable customer satisfaction (Y). And partial independents variable’s which consists of efficiency (X1), reliability (X2), and responsiveness (X5) have effect on customer satisfaction (Y). Contrary to other four dimensions fulfillment (X3), privacy (X4), compensation (X6), and contact (X7) have no effect on dependent variabel customer satisfaction (Y). Adjusted R Square Value = 0,415 means 41,5% of the costumer satisfaction can be explained by the independent variable in this research and as the amount over 58,5% which affected by other variables outside this research model. Keyword : e-SERVQUAL, customer satisfaction